Peritraumatic Assessment of Autobiographical Memory After Exposure to a Traumatic Event. Issue 6 (27th November 2017) - Billoux, Sophie; Voltzenlogel, Virginie; Telmon, Norbert; Birmes, Philippe; Arbus, Christophe
Abstract: Posttraumatic stress disorder (PTSD) is commonly acknowledged to be associated with reduced specificity of autobiographical memory (AM). However, very few studies have assessed AM in the peritraumatic phase. The aim of the present study was to examine whether the AM impairment reported in PTSD is present a few days after a traumatic event. We assessed AM in 41 participants who had recently been exposed to trauma, and 34 controls who had never experienced a traumatic situation. The trauma‐exposed participants also completed the Impact of Event Scale‐R (IES‐R), the Inventory of Peritraumatic Distress, and the Peritraumatic Dissociative Experiences Questionnaire. Results showed that autobiographical memories cued by negative words were significantly less specific in the group of trauma‐exposed participants than in the control group ( p = .008; d = 0.40). Thus, mild AM impairment was already present three days after trauma exposure, long before acute PTSD set in.